1996
DOI: 10.1002/(sici)1097-4652(199606)167:3<469::aid-jcp11>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia decreases constitutive nitric oxide synthase transcript and protein in cultured endothelial cells

Abstract: Endothelial cell-generated nitric oxide (NO) accounts in large part for the labile vasodilator termed endothelium-derived relaxing factor. Two distinct types of NO synthase exist: a "constitutive' type (cNOS), found in endothelial cells, and an "inducible' enzyme. Endothelial cells sense pO2 levels in the range of 70-20 torr and respond to this hypoxia by inducing transcription of genes which encode the vasoactive proteins PDGF-B and endothelin-1. Exposure of human or bovine endothelial cells to low oxygen ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Previous studies of NOS expression in systemic and pulmonary endothelial cells from different species in cultures [31,32,33,34,35,36,37] have yielded conflicting results. Recently, Toporsian et al [38] reported in vivo downregulation of eNOS mRNA and protein levels in the aorta of rats following prolonged hypoxia, which correlated with impaired endothelium-dependent vasorelaxation, whereas there was an increase in eNOS protein levels in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of NOS expression in systemic and pulmonary endothelial cells from different species in cultures [31,32,33,34,35,36,37] have yielded conflicting results. Recently, Toporsian et al [38] reported in vivo downregulation of eNOS mRNA and protein levels in the aorta of rats following prolonged hypoxia, which correlated with impaired endothelium-dependent vasorelaxation, whereas there was an increase in eNOS protein levels in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Expression and activity of eNOS, a main source of basal endothelial NO, have been reported to be upregulated (Arnet et al 1996; Le Cras et al 1998; Coulet et al 2003; Shirai et al 2003), downregulated (McQuillan et al 1994; Liao et al 1995; Phelan and Faller 1996; Laufs et al 1997; Toporsian et al 2000; Takemoto et al 2002), or unchanged (Murata et al 2001; Tahawi et al 2007) in various experimental models of hypoxia and repetitive hypoxia/reoxygenation. Contradictory reports of eNOS expression and activity appear to be due to temporal variations in experimental hypoxemic conditions, and differences in the species and vascular bed from which endothelial cells were derived.…”
Section: Repetitive Hypoxia/reoxygenationmentioning
confidence: 99%
“…Thus, control and regulation of the eNOS enzyme at the cellular level had previously been proposed to be chiefly through activation of specific cell surface receptors by calcium‐mobilizing agonists. However, we recently reported that exposure of endothelial cells to low (but physiological) oxygen tensions ( P O 2 = 20–40 mmHg) results in a profound decrease in the transcript for eNOS and a corresponding fall in eNOS protein levels 50 and co‐ordinate impairment of production of NO in response to stimulators of eNOS. Transition metals inhibited the hypoxic regulation of cNOS transcripts, suggesting a mechanism comparable to that by which oxygen tension regulates expression of other vasoregulatory genes, and new gene transcription is required for eNOS suppression by hypoxia.…”
Section: Vasoactive Genes Regulated By Hypoxiamentioning
confidence: 99%
“…Levels of cyclo‐oxygenase‐2 (COX‐2) mRNA and protein are increased by hypoxia 67 . In addition, hypoxia also decreases endothelial cell expression of genes encoding or producing a number of antimitogenic or antiproliferative agents, including eNOS 16 , 46 , 50 . Hypoxia reduces endothelial cell release of prostacyclin 68 and heparan sulphates, 69 , 70 which inhibit proliferation.…”
Section: Hypoxia and Tissue Remodellingmentioning
confidence: 99%